PROSES PSIKOLOGIS PENERIMAAN DIRI PADA MAHASISWA UIN SUNAN GUNUNG DJATI BANDUNG DARI MASA REMAJA MENJADI DEWASA - Putri, Aida Merisa Sutisna; Jannah, Nada Zahra Radhatul; Dhiya’ulhaq, Nakhwatunnisa; Saputra, Reza Mahendra Nunggal; Salsabillah, Sifa; Heryati, Yeti (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2026)
The process of self-acceptance from adolescence to early adulthood is certainly not easy, there will always be many problems faced by each individual and there are factors that influence them. These problems can include anxiety caused by people around you, many things you haven’t tried, and others. Meanwhile, the factors come from internal and external factors. These problems and factors make it difficult for individuals to accept the existing situation. Therefore, this research aims to find out how to solve the problems faced by each individual. The method used in this research uses quantitative methods.